Biomarkers to predict risk of venous thromboembolism in patients with rheumatoid arthritis receiving tofacitinib or tumour necrosis factor inhibitors. Issue 2 (2nd November 2022) - Weitz, Jeffrey I; Szekanecz, Zoltán; Charles-Schoeman, Christina; Vranic, Ivana; Sahin, Burak; Paciga, Sara A; Wang, Zhenyu; Hyde, Craig; Martin, David A
Abstract : Objective: In the ORAL (Oral Rheumatoid Arthritis triaL) Surveillance study of patients with rheumatoid arthritis aged ≥50 years with ≥1 additional cardiovascular risk factor, incidence of pulmonary embolism was higher with tofacitinib 10 mg two times per day than with tumour necrosis factor inhibitors (TNFi). This exploratory post hoc analysis examined whether biomarkers explained the associations of tofacitinib versus TNFi with venous thromboembolism (VTE). Methods: ORAL Surveillance was a prospective, open-label, event-driven, non-inferiority, postauthorisation safety study. Patients were randomised 1:1:1 to receive tofacitinib 5 mg or 10 mg two times per day or a TNFi. For this analysis, 294 soluble, proteomic, genetic and antibody biomarkers (of which 79 had a known role in inflammation, coagulation, vascular biology or Janus kinase signalling) were quantified in serum collected at baseline, month 12 and study end. Results: Overall, 4362 patients were randomised and treated. The exploratory biomarker data set included 285 patients (57 VTE cases; 228 matched controls). D-dimer was quantified in 3732 patients (54 VTE cases; 3678 controls). No biomarker demonstrated a clear mechanistic association with the increased risk of VTE for tofacitinib versus TNFi. Month 12 D-dimer levels were positively associated with risk of a subsequent VTE within the tofacitinib 5 mg and 10 mg two times per day arms. Conclusions: Overall, this post hoc analysis did not identify biomarkers that explained the increased VTE risk for tofacitinib versus TNFi. Individual VTE risk should be considered when making decisions about initiation or maintenance of tofacitinib treatment. Trial registration number: NCT02092467 ; ClinicalTrials.gov.